Mucoadhesive liquid crystal precursor system for photodynamic therapy of oral cancer mediated by methylene blue - Balian, Giovana Maria Fioramonti Calixto [UNESP]; Luiz, Marcela Tavares [UNESP]; Filippo, Leonardo Delello Di [UNESP]; Chorilli, Marlus [UNESP] (Elsevier, 2023)
Oral cancer is one of the most prevalent types of cancer head and neck cancers worldwide. Photodynamic therapy (PDT) has demonstrated great potential against cancers, reducing long-term morbidity. In this study, we investigated the incorporation of methylene blue (MB) in a mucoadhesive liquid crystal precursor system (LCPS) for oral cancer treatment. The photostability and the in vitro release, permeation, and retention profile of MB-loaded LCPS (MB-LCPS) were investigated, as well as its in vitro PDT activity against normal (HaCaT) and tumoral (HSC-3) cell lines. LCPS increased the photostability of MB and exhibited a prolonged release profile of MB. In addition, LCPS increased the retention of MB in the porcine esophageal mucosa by around 3 times higher than the MB solution. The retention of MB in LCPS was around 2 times greater than its permeability, which is suitable for guaranteeing the maintenance of the therapy in the oral cavity. In vitro cytotoxicity assay indicated that MB-LCPS increased the antitumoral activity of MB after 20 min of irradiation at 660 nm and 12.5 J/cm2. The results obtained suggest that the developed formulation is an interesting strategy for the potential application in the treatment of oral cancer by PDT.
Keywords: Buccal route; Drug delivery system; Liquid crystalline system; Photodynamic Therapy; Photosensitizer